Pain Symptoms in Fibromyalgia Patients with and without Provoked Vulvodynia. (28th January 2014) - Ghizzani, Anna; Di Sabatino, Valentina; Suman, Anna Lisa; Biasi, Giovanni; Santarcangelo, Enrica Laura; Carli, Giancarlo
Abstract : Objective . The aim of the study was to compare the pain symptoms of fibromyalgia patients exhibiting (FMS+PVD) and not exhibiting (FMS) comorbidity with provoked vulvodynia. Study Design . The case control study was performed in 39 patients who had been diagnosed with FMS and accepted to undergo gynaecological examination and in 36 healthy women (C). All patients completed standardized questionnaires for pain intensity, pain area, and psychological functioning. The gynaecological examination included vulvar pain pressure reactivity (Q-tip), pelvic tone assessment (Kegel manoeuver), and a semistructured interview collecting detailed information about pelvic symptoms and sexual function. Results . FMS+PVD patients displayed a higher number of associated symptoms than FMS patients. The vulvar excitability was significantly higher in FMS+PVD than in FMS and in both groups than in Controls. Half of FMS+PVD patients were positive to Kegel manoeuver and displayed higher scores in widespread pain intensity, STAI-Y2, and CESD levels than Kegel negative patients. Conclusions . The study reveals that increased vulvar pain excitability may occur in FMS patients independently of the presence of coital pain. Results suggest that coital pain develops in patients with higher FMS symptoms severity due to the cooperative effects of peripheral and central sensitization mechanisms.